Canadian Bolsheviks: The Early Years of the Commmunist Party of Canada - Angus, Ian (Trafford, 2004)
Canadian communism did not spring out of the ground suddenly at the end of World War I, and it was not smuggled into the country by Russian agents. The men and women who built the new movement were long-time socialist and labour militants in Canada. Inspired by the Russian Revolution and by their own experiences as leaders of the post-war labour revolt in Canada, they set about to create a new kind of party, one that could lead the fight for workers' power. The new Communist Party, formed between 1919 and 1921, quickly became the largest party on the left, with strong roots and influence in the unions and basic industry. Its members led heroic strikes. They fought for labor unity, and engaged in united electoral activity with other currents in the workers movement. They were in the forefront of the struggle for democratic rights. Ten years later, the party was destroyed. Most of its founding leaders were expelled, and three quarters of its membership dropped out. The Communist Party abandoned the program it had adopted in its early years, and turned its back on its principles. The organization still called itself Communist, but it was now "Tim Buck's Party." It had been transformed from a revolutionary party into an agent of the new ruling caste in Moscow. In Canadian Bolsheviks, Ian Angus describes and explains the first attempt to build a Leninist party on Canadian soil, showing why it succeeded so well at first, and why it ultimately failed. The second edition of a book that has been widely hailed as a pathbreaking work, "the best yet to appear" on the origins of Canadian communism. –Publisher's description
OCLC: 57575142

Survival: A Thematic Guide to Canadian Literature - Atwood, Margaret. (McClelland & Stewart, 2004)
When first published in 1972, Survival was considered the most startling book ever written about Canadian literature. Since then, it has continued to be read and taught, and it continues to shape the way Canadians look at themselves. Distinguished, provocative, and written in effervescent, compulsively readable prose, Survival is simultaneously a book of criticism, a manifesto, and a collection of personal and subversive remarks. Margaret Atwood begins by asking: "What have been the central preoccupations of our poetry and fiction?" Her answer is "survival and victims." Atwood applies this thesis in twelve brilliant, witty, and impassioned chapters; from Moodie to MacLennan to Blais, from Pratt to Purdy to Gibson, she lights up familiar books in wholly new perspectives. This new edition features a foreword by the author. –Publisher's description.
https://en.wikipedia.org/wiki/Survival:_A_Thematic_Guide_to_Canadian_Literature
Keywords: Canadian Literature; Criticism

Common and Contested Ground: A Human and Environmental History of the Northwestern Plains - Binnema, Ted (University of Toronto Press, 2004)
In Common and Contested Ground, Theodore Binnema provides a sweeping and innovative interpretation of the history of the northwestern plains and its peoples from prehistoric times to the Lewis and Clark Expedition. The real history of the northwestern plains between a.d. 200 and 1806 was far more complex, nuanced, and paradoxical than often imagined. Drawn by vast herds of buffalo and abundant resources, bands of Indians, fur traders, and settlers moved across the northwestern plains establishing intricate patterns of trade, diplomacy, and warfare. In the process, the northwestern plains became a common and contested ground. Drawing on a wide range of sources, Binnema examines the impact of technology on the peoples of the northern plains, beginning with the bow-and-arrow and continuing through the arrival of the horse, European weapons, Old World diseases, and Euroamerican traders. –Publisher's description
OCLC: 54692813
Keywords: Ethnic relations; Fourrures Commerce Grandes Plaines Histoire; Fur trade; Fur trade Great Plains History; Grandes Plaines Relations interethniques; Great Plains; Great Plains Ethnic relations; History; Indianen; Indians of North America; Indians of North America Commerce; Indians of North America Commerce Great Plains History; Indians of North America Great Plains History; Indiens d'Amérique Commerce Grandes Plaines Histoire; Indiens d'Amérique Grandes Plaines Histoire

Workplace Learning: A Critical Introduction - Bratton, John; Sawchuk, Peter H.; Helms Mills, Jean C.; Pyrch, Timothy (Garamond Press, 2004)
This innovative book is concerned with the power relations, complexities, and contradictions in the paid workplace. Workplace learning is not value-free or politically neutral, and cannot be studied independently of the political economy of work. [This book] is part of a growing body of work that offers an alternative to mainstream approaches to workplace learning, recognizing that power relations, politics and conflicts of interest all shape learning. The authors emphasize the lived experiences of working people, avoiding prescriptive accounts and uncritical Human Resource Development views. –Publisher's description. Contents: 1. Introduction – 2. Management strategies and workplace learning – 3. Groups, teams and workplace learning – 4. Organizational learning and learning organizations – 5. Unions and workplace learning – 6. Adult education, learning and work – 7. Toward the future of workplace learning. Includes bibliographical references (p. [181]-194) and index.
Keywords: Adult education; Employees; Experiential learning; Training of

Le quatuor d'asbestos : autour de la grève de l'amiante - Delisle, Esther; Malouf, Pierre K. (Éditions Varia, 2004)
Comme son titre l'indique, Le Quatuor d'Asbestos est composé de quatre livres, qui replacent dans son contexte historique la fameuse grève de l'amiante de 1949. De nombreux documents y sont présentés pour la première fois ; tous les points de vue y sont exprimés, car ici l'histoire est racontée par ceux qui l'ont vécue. On constatera, entre autres choses, que l'ouvrage publié en 1956 sous la direction de Pierre Trudeau, La Grève de l'amiante, donne une interprétation très réductrice, voire mensongère des causes et des conséquences de la grève. Tout commence donc en mars 1948 avec la publication dans la revue Relations d'un article retentissant du journaliste franco-américain Burton LeDoux sur les conditions de vie inhumaines des mineurs de Saint-Rémi d'Amherst dans les Laurentides. Cet article se veut la première étape dans une campagne pour l'amélioration de l'hygiène industrielle au Québec. Mais le gouvernement de Maurice Duplessis vient de céder le monopole du développement de l'Ungava aux intérêts financiers qui traitent comme du bétail les mineurs de Saint-Rémi. Avec la complicité de Mgr Joseph Charbonneau, les compagnies et le gouvernement musèlent Relations. Le Devoir prend alors le relais et publie en janvier 1949 un deuxième article de Burton LeDoux, qui révèle l'existence à East Broughton dans la région de l'amiante d'un autre abattoir humain. Un mois plus tard, la grève éclate à Asbestos et à Thetford Mines. La première revendication des mineurs : l'élimination de la poussière. Les travailleurs sont galvanisés, car c'est de leur santé et de leur vie mêmes qu'il s'agit. La grève durera quatre mois et demi, mais sera, surtout sur la question essentielle de l'hygiène industrielle, un échec total. Il faudra attendre 1975 pour qu'on décide enfin de corriger une situation qui aurait pu et dû l'être un quart de siècle plus tôt. Ensuite, il y aura la nationalisation et le déclin de l'industrie. Mais c'est une histoire qui n'a pas de fin et il se publie encore de nos jours des articles qui confirment que Burton LeDoux avait vu clair dès 1948. –Résumé de l'éditeur
OCLC: 858628003
Keywords: 1900-1999; Asbestos Strike; Québec; 1949; Grève de l'amiante; Québec; 1949; Grèves et lock-out Mines d'amiante Québec (Province) Histoire; Grèves et lock-out Mines d'amiante Québec (Province) Histoire Sources; Grèves et lock-out Mines d'amiante Québec (Province) Val-des-Sources; History; Québec; Québec Asbestos; Silicose; Silicose Québec (Province) Histoire 20e siècle; Silicosis; Silicosis Québec (Province) History 20th century; Sources; Strikes and lockouts Asbestos mining; Strikes and lockouts Asbestos mining Québec (Province) Asbestos; Strikes and lockouts Asbestos mining Québec (Province) History; Strikes and lockouts Asbestos mining Québec (Province) History Sources

The Paradox of American Unionism: Why Americans Like Unions More Than Canadians Do, But Join Much Less - Lipset, Seymour Martin; Meltz, Noah M.; Katchanovski, Ivan; Gomez, Rafael (ILR Press, 2004)
Why have Americans, who by a clear majority approve of unions, been joining them in smaller numbers than ever before? This book answers that question by comparing the American experience with that of Canada, where approval for unions is significantly lower than in the United States, but where since the mid-1960s workers have joined organized labor to a much greater extent. Given that the two countries are outwardly so similar, what explains this paradox? This book provides a detailed comparative analysis of both countries using, among other things, a detailed survey conducted in the United States and Canada by the Ipsos-Reid polling group. The authors explain that the relative reluctance of employees in the United States to join unions, compared with those in Canada, is rooted less in their attitudes toward unions than in the former country's deep-seated tradition of individualism and laissez-faire economic values. Canada has a more statist, social democratic tradition, which is in turn attributable to its Tory and European conservative lineage. Canadian values are therefore more supportive of unionism, making unions more powerful and thus, paradoxically, lowering public approval of unions. Public approval is higher in the United States, where unions exert less of an influence over politics and the economy. –Publisher's description
OCLC: 777771938
Keywords: Labor movement; Labor unions; Mouvement ouvrier; Syndicats; trade unions

Hidden Knowledge: Organized Labour in the Information Age - Livingstone, D. W.; Sawchuk, Peter H. (Peter Harold); Roth, Reuben N.; Martin, D'Arcy; Morgan, Clara (Garamond Press, 2004)
This book offers an original contribution to understanding an often-ignored aspect of our knowledge society and the much-heralded ‘knowledge-based economy.’ It decisively explodes the dual myths that working-class adults have inferior learning capacities and that talented youths naturally leave blue-collar careers. Livingstone and Sawchuk document the genuine learning practices of working-class people in unprecedented detail, using richly textured accounts of prior school experiences; current adult education course participation; and a wide array of learning resources in paid workplaces, households, and community settings. The authors criticize dominant theories of learning and work and develop an alternative explanation of working-class adult learning. Their analysis, grounded in the specific practices of everyday life, pays careful attention to the ways in which differential economic power, labor processes, sectoral contexts, union cultures, and access to organized educational resources shape individual and collective learning activities. The book also provides a reflective discussion of research processes suitable for democratic knowledge production in partnership with workers and their organizations, as well as workers' own practical recommendations for changes in learning and work relations. –Publisher's description. Contents: Introduction: Dimensions of learning and work in the knowledge society – Pt. 1. Researching learning and work. Starting with Workers and Researching the "Hard Way" / with D'Arcy Martin – Beyond cultural capital theories: Hidden dimensions of working-class learning. Pt. 2. Case studies. Auto workers: Lean manufacturing and rich learning / with Reuben Roth – Building a workers' learning Culture in the Chemical Industry – Learning, Restructuring and job segregation at a community college – Divisions of labour / Divisions of learning in a small parts manufacturer – Garment workers: learning under disruption / with Clara Morgan. Pt. 3. Comparative perspectives across case studies. Household and community-based learning: Learning cultures and class differences beyond paid work – Surfacing the hidden dimension of the knowledge society: the struggle for knowledge across differences. Includes bibliographical references (p. [299]-309) and index.
Keywords: Adult learning; Canada; Case studies; Education; Information society; Interviews; Labor union members; Labor unions; Occupational training; Working class - Effect of technological innovations on

Racism, Eh?: A Critical Inter-Disciplinary Anthology of Race and Racism in Canada - Nelson, Charmaine; Nelson, Camille A. (Captus Press, 2004)
"Racism, Eh?" is the first publication that examines racism within the broad Canadian context. This anthology brings together some of the visionaries who are seeking to illuminate the topics of race and racism in Canada through the analysis of historical and contemporary issues, which address race and racism as both material and psychic phenomena. Fundamentally interdisciplinary in nature, this text will be an invaluable resource for undergraduate and graduate students, academics studying or practicing within the Humanities and the Social Sciences, and anyone seeking information on what has been a little explored and poorly understood Canadian issue."–Publisher's description. Contents: Part 1 Institutional Racism – 1 Penn and Teller Magic – 2 Lance Belanger's Tango Lessons – 3 The Black Occupational Structure in Late-Nineteenth-Century Ontario – Part 2 Crime and Justice – 4 Raising Raced and Erased Executions in African-Canadian Literature – 5 Examining Racism and Criminal Justice – 6 Criminological Research on "Race" in Canada – Part 3 First Nations – Of Land, Law and Power – 7 Across a Boundary of Lava – 8 Treaty Federalism – 9 Navigating Discrimination – Part 4 Race, Place and Nation – 10 Adrift in the Diaspora – 11 Racism Between Jews – 12 Local Colour – Part 5 Complexity of Intersectionallity and Performance of Racial Identity – 13 Speak White! – 14 Jack Canuck Meets John Chinaman – 15 Performing Desire – Part 6 Popular Culture – 16 Race In-Out of the Classroom – 17 Other Canadian Voices – 18 (Re)Visioning Histories – Part 7 Production and Representation – 19 Each Sentence Realized or Dreamed Jumps Like a Pulse with History and Takes a Side – 20 Articulating Spaces of Representation – 21 The "Hottentot Venus" in Canada – 22 Racial Recognition Underpinning Critical Art – Part 8 Multiculturalism – 23 But Where Are You REALLY From? – 24 Social Cohesion and the Limits of Multiculturalism in Canada – 25 Racialising Culture-Culturalising Race – 26 Re-articulating Multiculturalism.
Keywords: Racism – Canada

CCF Colonialism in Northern Saskatchewan: Battling Parish Priests, Bootleggers, and Fur Sharks - Quiring, David M. (UBC Press, 2004)
Saskatchewan's Co-operative Commonwealth Federation (CCF) the forerunner of the NDP, is often remembered for its humanitarian platform and its pioneering social programs. But during the twenty years it governed, it wrought a much less scrutinized legacy in the northern regions of the province." "Until the 1940s, churches, fur traders, and other influential newcomers held firm control over Saskatchewan's northern region. Following its rise to power in 1944 the CCF made aggressive efforts to unseat these traditional powers and install a new socialist economy and society in largely Aboriginal communities. The next two decades brought major changes to the region as well-meaning government planners grossly misjudged the challenges that confronted the north and failed to implement programs that would meet its needs. Northerners lacked the voice and political clout to determine policies for their half of the province and the CCF effectively created a colonial apparatus, imposing its own ideas and plans in those communities without consulting residents. While it did ensure that parish priests, bootleggers, and fur sharks no longer dominated the north, it failed to establish a workable alternative." "In written history that documents the colonial relationship between the CCT and northern Saskatchewan, David Quiring draws on extensive archival research and oral history to offer a fresh look at the CCF era. This examination will find an audience among historians of the north. Aboriginal scholars and general readers interested in Canadian history."–Publisher's description. Contents: Pt. 1. At the crossroads – 1. Another country altogether – Pt. 2. Building the colonial structure – 2. From the top – 3. Ultimate solution – 4. Deterrent to development – Pt. 3. Segregated economy – 5. Never before have we been so poor – 6. At the point of a gun – 7. Just one jump out of the stone age – 8. Pre-industrial way of life – Pt. 4. Poverty-stricken and disease-ridden – 9. Scarcely more than palliative – 10. Dollars are worth more than lives – Epilogue : we will measure our success – A. Comments on collection of oral history – B. Electoral record.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/ccfcolonialismin0000quir OCLC: 54372983
Keywords: Saskatchewan; Socialism

Le syndicalisme québécois : deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Contrairement à ce qu’on a cru pendant longtemps, l’histoire du syndicalisme au Québec remonte au début du XIXe siècle et évolue sensiblement au même rythme que celle des autres mouvements syndicaux en Amérique du Nord. À ce chapitre, les facteurs économiques et géographiques qui la rattachent au continent pèsent aussi lourd que le caractère distinct de la société québécoise. Voilà un des éléments clés qui ressortent du vaste pano-rama du syndicalisme au Québec que Jacques Rouillard trace ici. À chacune des périodes étudiées, qui renvoient aux grands moments de l’histoire occidentale, l’auteur montre comment les syndicats ont représenté une composante essentielle de la classe ouvrière et l’un des principaux lieux de contestation de l’ordre établi. Ce livre est une nouvelle édition de la première synthèse sur le syndicalisme québécois que Jacques Rouillard faisait paraître au Boréal en 1989. Ce nouveau texte, entièrement refondu, a été augmenté non seulement pour relater les événements qui se sont déroulés de 1985 à 2003, mais également pour tenir compte, aux diverses époques, des fruits de la négociation collective et de l’avancement de la recherche historique dans ce domaine. –Résumé de l'éditeur
https://www.editionsboreal.qc.ca/catalogue/livres/syndicalisme-quebecois-1243.html

Challenging the Market: The Struggle to Regulate Work and Income - Stanford, Jim; Vosko, Leah F. (McGill-Queen's University Press, 2004)
Challenging the Market offers insights from eighteen scholars and activists from around the world. Calling on a tremendous range of experience in different countries, different industries, and with different groups of workers, contributors argue that labour market policy should shift to a more interventionist and compassionate footing. For two decades economic and social policy in most of the world has been guided by the notion that economies function best when they are fully exposed to competitive market forces. In labour market policy, this approach is reflected in the widespread emphasis on "flexibility" - a euphemism for the retrenchment of income support and social security, the relaxation of labour market regulations, and the enhanced power of private actors to determine the terms of the employment relationship. These strategies have had marked effects on labour market outcomes, leading to greater vulnerability and polarization - and not always in ways that enhance worker-centred flexibility. The authors offer a more balanced analysis of the functioning and effects of labour market regulation and deregulation. By questioning the underpinnings of the "flexibility" paradigm, and revealing its often damaging impacts (on different countries, sectors, and constituencies), they challenge the conclusion that unregulated market forces produce optimal labour market outcomes. The authors conclude with several suggestions for how labour policy could be reformulated to promote both efficiency and equity. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/challengingmarke0000unse_l6i3
Keywords: Emploi; Employment (Economic theory); Labor costs; Labor demand; Labor market; Labor policy; Labor supply; Main-d'œuvre Coût; Marché du travail; Travail Politique gouvernementale; employing

Fighting for Dignity: The Ginger Goodwin Story - Stonebanks, Roger (Canadian Committee on Labour History, 2004)
Roger Stonebanks traces the life of charismatic labour leader Ginger Goodwin from his childhood in the Yorkshire Coalfields, through his mining career in Cape Breton and British Columbia, until his untimely and controversial death in the woods of Vancouver Island. Using archival research and contemporary accounts, Stonebanks explores the historical context that surrounded Goodwin's meteoric rise in BC's labour and socialist ranks. His life, from union hall to the soccer pitch, sheds light on working-class culture in resource communities in the early years of the 20th century. Ginger Goodwin was killed while trying to evade conscription during World War I. The Military police officer responsible claimed he shot only in self-defence, but rumors have since persisted that foul play was involved in the death of the prominent socialist and labour activist. Goodwin's own words explain his opposition to conscription and war, while Stonebanks examines the background and attitude of the police officers hunting down draft dodgers. Adrian Brooks provides a legal analysis and review of the case of His Majesty the King v. Daniel Campbell and how the trial might have unfolded — if there had been a trial of Constable Campbell. Written in engaging and accessible prose, the book features several never before published photographs. –Publisher's description
https://archive.org/details/fightingfordigni0000ston
Keywords: British Columbia; Draft resisters; Goodwin; Ginger; Labor Unions; Labor leaders; Officials and employees; WORLD War; 1914-1918; World War; 1914-1918

Saskatchewan: The Roots of Discontent and Protest - Warnock, John W. (Black Rose Books, 2004)
Isolation is part of the psyche of this sparsely populated prairie province, and this abundance of great open space has uniquely shaped the people, their politics, their economy and their relationship with the rest of North America. Using the broad, interdisciplinary social science approach of political economy analysis, Warnock traces Saskatchewan's past in an attempt to understand the present and glimpse some of its future. Along the way, he tells the story of Saskatchewan, from inception to centennial. –Publisher's description
Keywords: Economic conditions; Political culture; Politics and government; Social conditions